2017
DOI: 10.1016/j.yebeh.2016.12.027
|View full text |Cite
|
Sign up to set email alerts
|

The long-term course of temporal lobe epilepsy: From unilateral to bilateral interictal epileptiform discharges in repeated video-EEG monitorings

Abstract: Introduction: Bilateral interictal epileptiform discharges (IED) and ictal patterns are common

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
3
11
0
3
Order By: Relevance
“…Hypothetically, bilateral epileptiform activity may be due to secondary epileptogenesis with broadening of the epileptogenic network [30,31], associated with longer seizure duration and especially higher seizure frequency as seen in animal models [32]. Conversely, we did not find any effect of epilepsy duration and seizure frequency on the distribution of either ictal seizure patterns or on interictal epileptiform activity, in line with others [33,34]. Yet, we found preoperative secondary generalized seizures to be associated with the occurrence of bilateral ictal and interictal epileptiform activity, presumably reflecting preexisting widespread network of epileptic pathologic circuits [34].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Hypothetically, bilateral epileptiform activity may be due to secondary epileptogenesis with broadening of the epileptogenic network [30,31], associated with longer seizure duration and especially higher seizure frequency as seen in animal models [32]. Conversely, we did not find any effect of epilepsy duration and seizure frequency on the distribution of either ictal seizure patterns or on interictal epileptiform activity, in line with others [33,34]. Yet, we found preoperative secondary generalized seizures to be associated with the occurrence of bilateral ictal and interictal epileptiform activity, presumably reflecting preexisting widespread network of epileptic pathologic circuits [34].…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, we did not find any effect of epilepsy duration and seizure frequency on the distribution of either ictal seizure patterns or on interictal epileptiform activity, in line with others [33,34]. Yet, we found preoperative secondary generalized seizures to be associated with the occurrence of bilateral ictal and interictal epileptiform activity, presumably reflecting preexisting widespread network of epileptic pathologic circuits [34]. A further reason for the development of bilateral epileptiform discharges might be the epileptic spread initiating secondary seizure foci [35].…”
Section: Discussionsupporting
confidence: 76%
“…However, the accumulated evidence suggests that early surgical therapy is recommended for patients with DRE, especially with structural epilepsy such as MTLE with hippocampal sclerosis, cavernous malformations, or a benign tumor (44,(48)(49)(50). Furthermore, long-term unilateral TLE reportedly induces bilateral epileptogenicity (secondary epileptogenesis) and an unfavorable postsurgical outcome (51). Therefore, if we could have performed epilepsy surgery on the present case at a much earlier stage, for example, before the age of 10 years when the cat exhibited the minor seizure type, it might have been possible to inhibit secondary epileptogenicity and provide a better postoperative seizure outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these reports found that longer epilepsy duration (more than 20 years) was related to poorer outcomes after surgery while others found no relation between these parameters (37,(41)(42)(43). Although some authors suggested the possibility of secondary epileptogenesis in TLE (44)(45)(46), this hypothesis needs to be proved in future studies (47). Regarding the fact that both groups in our study had a longer epilepsy duration than 20 years, we consider that the effect of age does not play an important role in our results.…”
Section: Discussionmentioning
confidence: 99%